Credit Dependency and Debt Management: A Bibliometric Review - Judijanto, Loso; Coryanata, Isma; Novitasari, Salwa Aulia (West Science Interdisciplinary Studies, 2025)
This study presents a comprehensive bibliometric analysis of scholarly literature on credit dependency and debt management, aiming to map the intellectual, thematic, and collaborative structures that define the field. Using data extracted from the Scopus database and analyzed through VOSviewer, the study identifies major research clusters including financial management, debt provision, and risk management. The findings highlight a clear evolution in research focus—shifting from individual financial behaviors and literacy toward institutional credit risk management and systemic financial governance. Co-citation and author network analyses reveal key contributors such as Lusardi, Altman, and Duffie, representing distinct but interconnected scholarly traditions. Moreover, country collaboration mapping positions the United States as the most central hub, with growing contributions from emerging economies. This study not only synthesizes the knowledge base but also reveals thematic gaps and opportunities for future interdisciplinary research. It contributes valuable insights for academics, policymakers, and practitioners seeking to understand and address the global challenges associated with credit reliance and sustainable debt management.